Aromatization of alkenes by gallium/H-ZSM-5 zeolite catalysts - Nash, Robin John (Centre for Catalysis Research, 2016)
Gallium/H-ZSM-5 zeolite catalysts have been extensively researched for the aromatization of liquified petroleum gas (LPG). In 1989 BP and UOP collaborated to commission a pilot plant in Grangemouth, Scotland, for the aromatization of propane and butane. This plant, based on a technology called the Cyclar process, used continuous catalyst regeneration (CCR) and a gallium impregnated ZSM-5 zeolite catalyst to achieve yields of ca. 65% aromatics, mainly benzene, toluene and xylenes (BTX) [Guisnet and Gnep, 1992]. As a result of the Fischer-Tropsch process used by SASOL Ltd., South Africa is in an internationally unique position, in that it has a surplus of long chain linear alkenes with carbon numbers in the range C6-C8 . There could be large economic incentives to convert these alkenes into more valuable products, like alcohols or aromatics. Thus the purpose of this project was to determine if gallium/H-ZSM-5 catalysts, similar to those used in the Cyclar process, would be suitable for the aromatization of long chain alkenes. Three methods were investigated for the introduction of gallium into ZSM-5: (i) physical mixing with gallium oxide; (ii) impregnation by incipient wetness with gallium nitrate; (iii) ion-exchange with gallium nitrate. The catalysts were. tested with regard to their catalytic activity for the aromatization of 1-hexene and 1-octene.